The P4’ Peptide-Carrying Bacillus subtilis in Cottonseed Meal Improves the Chinese Mitten Crab Eriocheir sinensis Innate Immunity, Redox Defense, and Growth Performance - Chao-Fan He; Wei Xiong; Xiang-Fei Li; Guang-Zhen Jiang; Ling Zhang; Zi-Shang Liu; Wen-Bin Liu (Aquaculture Nutrition)
This study developed a recombinant Bacillus subtilis to carry the LGSPDVIVIR peptide (cmP4) isolated from the hydrolyzed products of cottonseed meal with excellent antioxidant and immune-enhancing properties in vitro. It was carried as a tandem of five cmP4 peptides (cmP4’) to be stably expressed on a large scale. Then, its effectiveness was evaluated in Chinese mitten crab (Eriocheir sinensis) based on growth performance, redox defense, and innate immunity. A total of 280 crabs (mean body weight: 41.40 ± 0.14) were randomly assigned to seven diets including a control one (without B. subtilis) and six experimental ones with different doses (107,108, and 109 CFU/kg) of unmodified and recombinant B. subtilis, respectively, for 12 weeks. Each diet was tested in four tanks of crabs (10/tank). In terms of bacterial dosages, the final weight (FW), weight gain (WG), hemolymph and hepatopancreatic activities of superoxide dismutase (SOD), catalase (CAT), lysosome (LZM), acid phosphatase (ACP) and alkaline phosphatase (AKP), and hepatopancreatic transcriptions of cat, mitochondrial manganese superoxide dismutase (mtmnsod), thioredoxin-1 (trx1), and prophenoloxidase (propo) all increased significantly with increasing B. subtilis dosages, while hemolymph and hepatopancreatic malondialdehyde (MDA) content and the transcriptions of toll like receptors (tlrs), NF-κB-like transcription factor (relish), and lipopolysaccharide-induced TNF-α factor (litaf) all decreased remarkably. In terms of bacterial species, the recombinant B. subtilis group obtained significantly high values of FW, WG, hemolymph, and hepatopancreatic activities of SOD, CAT, LZM, ACP, and AKP, and the transcriptions of mtmnsod, peroxiredoxin 6 (prx6), and propo compared with the unmodified B. subtilis, while opposite results were noted in hemolymph and hepatopancreatic MDA content and the transcriptions of tlrs, relish, and litaf. These results indicated that dietary supplementation with 109 CFU/kg of recombinant B. subtilis can improve the growth performance, redox defense, and nonspecific immunity of E. sinensis.